Maximizing Queueing Network Utility Subject to Stability: Greedy Primal-Dual Algorithm - Stolyar, Alexander L. (Queueing systems, 2005)
We study a model of controlled queueing network, which operates and makes control decisions in discrete time. An underlying random network mode determines the set of available controls in each time slot. Each control decision "produces" a certain vector of "commodities"; it also has associated "traditional" queueing control effect, i.e., it determines traffic (customer) arrival rates, service rates at the nodes, and random routing of processed customers among the nodes. The problem is to find a dynamic control strategy which maximizes a concave utility function H ( X ), where X is the average value of commodity vector, subject to the constraint that network queues remain stable.